Using participatory rural appraisal (PRA) in the identification of children with disabilities in rural Kilifi, Kenya. - Gona, J; Hartley, S; Newton, C (2006)
INTRODUCTION: Cross-sectional surveys have been used widely for identifying children with disabilities, but they have several disadvantages. The surveys concentrate on identifying impairments and do not encourage the participation and ownership of the community. Participatory rural appraisal (PRA) provides a cost-effective and efficient method that reflects the local perceptions of disability and involves local people. These factors are important for sustainability in resource-poor countries. PURPOSE: To evaluate the application of PRA to identifying children with disabilities in a rural setting. METHODS: PRA was used to identify children with disabilities in two rural sub-locations in Kilifi, Kenya. Data were collected through 12 focus group discussions and 12 social mapping activities. A purposive convenience sample of teachers, village leaders and women groups participated in the PRA. The perceptions of disability were established before identification of the children. The categories of identification were based on these local perceptions. The qualitative data were analyzed thematically and validation was performed through triangulation. RESULTS: Disability was perceived locally as the existence of impairments, activity limitations and participation restrictions. Disabilities were associated with traditional beliefs including witchcraft, evil spirits and punishments from God. In some cases these categories were mutually exclusive and in others they were concurrent. Children who had lost their parents and were not being cared for by relatives (disadvantaged orphans) were also perceived as disabled children by teachers and local women, but not by community leaders. CONCLUSION: The results suggest that PRA is an efficient and cost-effective method of identifying children with disabilities according to local perceptions, and it may be useful in community-based rehabilitation as an alternative to surveys.